Jumping the hurdles in making new venture: The mediating role of marketing self-efficacy in start-up intention - Jung-Rae Kim (Global Business & Finance Review (GBFR), 2023)
Purpose: The purpose of this study is to examine marketing self-efficacy as a mediator in the resilience and start-up intention relationship. Design/methodology/approach: Questionnaires were employed to collect data from potential entrepreneurs in Korea. A total of 280 completed questionnaires were returned. Multiple regression analysis was used to test the hypothesis. Findings: Results showed that resilience and marketing self-efficacy had a positive effect on start-up intention. Further, marketing self-efficacy had a significant mediating effect on the resilience and start-up intention relationship. Research limitations/implications: This study empirically confirmed that resilience and marketing self-efficacy are important drivers of start-up intention, and it is also necessary to create an educational program that can increase the level of resilience and marketing self-efficacy. Originality/value: The present study investigates how resilience promotes firm creation, but scholars have not begun to identify specific mechanisms. The findings of this study are valuable for broadening resilience research by identifying the mediating mechanism of marketing self-efficacy between the relationship between resilience and start-up intention. This study suggests that universities and other organizations involved with potential entrepreneurs should create educational programs that can increase resilience and marketing self-efficacy
Keywords: 650; Resilience; Marketing self-efficacy; Potential entrepreneur; Start-up intention